ANALYSIS OF INFERENTIAL UNDERSTANDING ABILITY OF STUDENTS GRADE 6 IN SD MUTIARA BUNDA (International Conference on Elementary Education, 2018)
The purpose of this study was to (1) determine the inferential understanding ability of student grade 6 in reading comprehension of narrative texts; (2) find the barriers of students in concluding the narrative text content; (3) knowing the efforts made by the teacher in developing inferential understanding of students. The method used in this study is a qualitative research method. The subjects in this study were students in grade VI SD Mutiara Bunda in the Bandung city. Data collection methods in this study are using tests, interviews and documentation. The results of this study are (1) the inferential understanding ability of the sixth grade students of SD Mutiara Bunda is included in the low category; (2) the resistance of students in concluding the contents of the story is that students find it difficult to rewrite the story in a coherent way; (3) the efforts made by the teacher in developing students' inferential understanding of the narrative text discourse are guiding students in reading comprehension and providing motivation to students.